2022
DOI: 10.3233/jnd-210768
|View full text |Cite
|
Sign up to set email alerts
|

Real-world Adherence to Nusinersen in Adults with Spinal Muscular Atrophy in the US: A Multi-site Chart Review Study

Abstract: Limited evidence exists on real-world adherence to nusinersen for the treatment of spinal muscular atrophy (SMA). Data are presented from a multi-site retrospective chart review of 86 adults with SMA initiating nusinersen at nine US centers between January 2017 and February 2019. Seventy-nine (92%) adults remained on nusinersen during the study; 454 (92%) of 493 total nusinersen doses were received on time. Fifty-eight (67%) adults received all nusinersen doses on time. The majority of patients with at least o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 23 publications
3
14
2
Order By: Relevance
“…Elman et al conducted an analysis of a retrospective chart review using a limited set of Electronic Medical Record (EMR) data from nine Muscular Dystrophy Association (MDA) clinics and used the same grace periods as this study. In contrast to our findings, Elman et al found that 58 patients (67% of cohort) were adherent at 24 months and 92% of doses were administered on schedule when doses were considered cumulatively across all patients [24]. Certain study design aspects of the analysis by Elman et al may have contributed in part to the differences in the adherence observed compared with this analysis.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Elman et al conducted an analysis of a retrospective chart review using a limited set of Electronic Medical Record (EMR) data from nine Muscular Dystrophy Association (MDA) clinics and used the same grace periods as this study. In contrast to our findings, Elman et al found that 58 patients (67% of cohort) were adherent at 24 months and 92% of doses were administered on schedule when doses were considered cumulatively across all patients [24]. Certain study design aspects of the analysis by Elman et al may have contributed in part to the differences in the adherence observed compared with this analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…Elman et al found that 92% of patients with SMA were persistent with nusinersen treatment at 24 months [24]. In contrast, and similar to the present study results, Gauthier-Loiselle et al [25] reported that \ 50% of patients, regardless of SMA type, remained on treatment 2 years after starting nusinersen.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations